2018
DOI: 10.3788/col201816.080101
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of underwater optical wireless power transfer using a laser diode

Abstract: We experimentally demonstrate an underwater optical wireless power transfer (OWPT) using a laser diode (LD) as a power transmitter. We investigate the characteristics of a solar cell and a photodiode (PD) as a power receiver. We optimize the LD, the PD, and the solar cell to achieve the maximum transfer efficiency. The maximum transfer efficiency of the back-to-back OWPT is measured as 4.3% with the PD receiver. Subsequently, we demonstrate the OWPT in tap and sea water. Our result shows an attenuation of 3 dB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…With corrections, efficiencies of 40–60% are possible, according to [ 61 ]. An underwater LPT setup was tested [ 62 ], resulting in an overall efficiency of 4%. The laser output power corresponded with 50 m .…”
Section: Electromagnetic Uncoupled Technologiesmentioning
confidence: 99%
“…With corrections, efficiencies of 40–60% are possible, according to [ 61 ]. An underwater LPT setup was tested [ 62 ], resulting in an overall efficiency of 4%. The laser output power corresponded with 50 m .…”
Section: Electromagnetic Uncoupled Technologiesmentioning
confidence: 99%
“…Regarding underwater optical link transmission, very few experiments can be found in the literature [56][57][58]. All of these could achieve power transfers in the mW range, with a power transfer efficiency below 20% for distances over 1 m. Regarding data transfer, in [57], the authors achieved data rates up to 60 Mbps at the receiver side, at a distance of 2.3 m from the emitter.…”
Section: Optical Linkmentioning
confidence: 99%
“…ηop of the 532 nm laser was the highest; however, the ηop of the 635 nm laser in summer was the highest due to the increase in the proliferation of phytoplankton because of the temperature rise in seawater and the increased sunshine hours. As explained above, the light reaching rate varies depending on location [8][9][10][11][12][13][14], season [24], and depth of seawater collection [12]. In this study, deep seawater and tap water were prepared to reproduce the seafloor exploration environment.…”
Section: Refmentioning
confidence: 99%
“…However, as shown in Figure 1, the attenuation rate of the 532 nm green laser was the lowest, although there were some differences depending on the seawater sampling area [22,23]. With the recent confirmation of the existence of marine resources on the seafloor, the OWPT system has also been researched in anticipation of under water and seawater exploration [10][11][12][13]. Miyamoto et al reported that a GaAs solar cell was irradiated with 450 nm laser light at 6 W through a fly-eye lens in a 90 cm long water tank, and the power was converted to 0.755 W. [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation